Long‐Term Outcome (10 Years) of Multiple Recession‐Type Defects Treated With Acellular Dermal Matrix Graft and Coronally Advanced Flap: A Case Report. Issue 3 (12th April 2019) - Schinini, Guillermo; Romanelli, Hugo; Chambrone, Leandro
Abstract : Introduction: There is limited evidence related to the long‐term treatment outcomes of acellular dermal matrix graft (ADMG) plus coronally advanced flap (CAF) for the treatment of multiple recession defects. The aim of this case report is to assess the short‐ and long‐term clinical outcomes of Miller Class I multiple gingival recession‐type defects in the maxilla treated with ADMG plus CAF. Case Presentation: A 36‐year‐old female patient smoking < five cigarettes per day presented multiple adjacent Miller Class I gingival recession in the left maxilla and was referred for treatment with chief complaints of dental hypersensitivity and esthetics. Root coverage was achieved by ADMG + CAF and the patient underwent a 10‐year follow‐up. Conclusions: Within the limits of this case report, mean root coverage obtained at 6 months could not be maintained in the long term. A significant relapse was detected after 10 years, from 80% complete root coverage (CRC) at 6 months to 40% at 10 years. Monitoring, compliance, and reinstructions in oral hygiene techniques seem mandatory for minimizing relapse of gingival recessions after root coverage procedures.